Desenvolvimento de óvulo, fruto e semente de Xyris (Xyridaceae, Poales) - Nardi, Kaire de Oliveira [UNESP] (2014)
Xyris is the largest genus of Xyridaceae, however there are few studies on its embryology and seed micromorphology. This thesis aimed to describe the development of ovule, fruit and seed of Xyris species in a comparative approach and to characterize the seed coat, identifying useful characters for taxonomy. The results show an embryological pattern for the genus: orthotropous, bitegmic and tenuinucellate ovules, with a micropyle formed by both the endostoma and exostoma; helobial, starchy endosperm; reduced, campanulate and undifferentiated embryo; seed coat formed by a tanniferous endotegmen, endotesta with thickwalled cells and exotesta with thin-walled cells; and a micropylar operculum. The pericarp is composed of a mesocarp with cells containing starch grains and an exocarp and endocarp formed by U-shaped thickened cells. The megagametophyte development differs among the studied species: it can be of the Polygonum or Allium type. The pericarp anatomy also varies since either the endocarp or the exocarp can have larger cells. The anatomy of the seed coat and pericarp in Xyris is first characterized here, as well as the origin of the operculum. Xyris differs from the other genera of Xyridaceae by the presence of orthotropous ovules, megagametophyte development of the Allium type, and seed coat composed of endotegmen, endotesta and exotesta, corroborating the division of the family into two subfamilies. The seed morphology and micromorphology show that the presence of longitudinal ridges in the seed coat is a pattern for the genus and that the following characters distinguish among the species: shape and size of the seed, shape of the ridges, number of cell rows between the ridges, and the striation pattern of the seed coat. Based on these characters a standard terminology is proposed to characterize the seed coat in the family